EVALUATION OF EQUIPMENT EDUCATION PROGRAM PACKAGE C (Evaluative Study in the Non-Formal Education Unit - Lebong Regency Learning Activity Center) - Wisnu Widyarthika; Johanes Sapri (DIADIK, 2019)
This study aims to describe the Package C equality education program which includes: 1) The context, input, process, and product of the Package C program. This research use desciptive qualitative approach. Data collection is done by the method of observation, interviews, and documentation. Proof of the validity of the data using triangulation techniques. Analysis of the data used is qualitative analysis with steps of data collection, data reduction, and conclusion drawing. The research results obtained in this study are: 1) Evaluation of the context of the Package C education program includes: the level of community needs for package C equality education programs and the socio- economic conditions of students; 2) Evaluate the input equivalence education package Package C, program organizers, competent tutors, curriculum, and facilities and infrastructure that are still lacking, and funding for the implementation of the package C program; 3) Evaluation of the process of the Package C education program includes: Schedule of learning activities, appropriate learning methods and models, motivation for learning citizens, and learning media used; 4) Product (product) equality of the Package C education program evaluation results from the implementation of programs and benefits of the C package equality education program for the community.